Effect of urban morphology on subtropical humid microclimate - Jain, Megha; Pathak, K.K. (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
In a humid subtropical atmosphere, urbanisation leads to increased thermal stress. The outside thermal stress depends on the flexibility of the geometrical arrangement of the buildings and its morphology and also materials to absorb solar radiation (albedo). The purpose of this study is to look at the influence of the morphology and water bodies on the microclimate of Bhopal, a town in central India. In this study the impact of urban morphology on microclimate is assessed through filed measurements. The field measurements included ambient air temperatures, humidity and wind speed. These metrological parameters were measured at nine sites in which three are in the old city, four in a new city and two sites falls in the suburbs. All three types of sites differed in terms of the building height by street width (H/W) ratio, ground cover, and distance to the lakes. In urban areas air high-temperature differences were mostly found during daytime. A highest intra-urban dissimilarity of 6ºC has been traced on clear days. Within the urban areas, the humidity was found normal (up to25-30%), and showed little diurnal variation. Few other factors that affected the temperature were also observed and are discussed in this paper.
The case of Bhopal, India
Keywords: Urban heat island; Urban geometry; Subtropical climate; Climate-sensitive urban design; Bhopal city morphology